Direct Cash Transfers to Youths’ Personal Bank Accounts and Unintended Consequences for Community Development - Ugo Chuks Okolie; Anthony C. Nwokolobia (Universitas Muhammadiyah Ponorogo, 2027)
In recent times, transferring cash directly to youths’ personal accounts has become a common strategy for poverty reduction and empowerment in many developing societies. Although this initiative aims to boost local economic activities and encourage self-reliance, growing evidence suggests that it may also have unintended adverse effects. This study examines the paradoxical effects of youth-targeted cash transfers to personal bank accounts on community development. Anchored on Dependency Theory, it contends that direct cash transfers to youths’ personal accounts can create dependency, diminish productive engagement, and erode communal responsibility among recipients. Using a qualitative research approach, data were collected and analyzed through content analysis to uncover underlying patterns. Findings show that while the scheme offers short-term financial relief and stimulates consumption, it also results in poor fund management, declining interest in entrepreneurship, and widening social inequality in the community. Furthermore, some beneficiaries exhibited reduced participation in collective development efforts, weakening the communal cohesion vital for sustainable growth. The study concludes that true community development is not achieved merely by distributing money but through capacity building, responsible engagement, and collective action. When direct cash transfers are paired with education, mentorship, and participatory governance, they have the potential to turn youths into active agents of social and economic change. It therefore recommends, among others, that such an initiative be complemented with skills training, financial literacy education, and community-based monitoring mechanisms to ensure responsible utilization and sustainable impact. The study is limited by its reliance on restricted data sources and context-specific evidence, which may reduce the depth and generalizability of its findings. It largely focuses on short-term outcomes, with limited longitudinal analysis of the long-term effects of direct cash transfers on youth behavior and community development. In addition, the absence of comparative analysis with alternative youth empowerment strategies and insufficient attention to institutional and governance frameworks weaken the study’s explanatory power. Potential respondent bias from self-reported data also affects the reliability of findings. To enhance sustainability, future research should adopt mixed-method and longitudinal approaches, expand coverage across diverse regions, and compare cash transfers with other development interventions. Greater focus should be placed on governance structures, community-level impacts, and theoretical frameworks related to sustainable development and social capital. Policy-oriented evaluations emphasizing monitoring, accountability, and complementary support mechanisms will further strengthen future studies. Keywords : Direct Cash Transfers; Youth Empowerment; Community Development; Socio-economic Implications; Dependency Theory;